Racial Disparities in Comorbidities, Complications, and Maternal and Fetal Outcomes in Women With Preeclampsia/eclampsia. (2nd October 2015) - Shahul, Sajid; Tung, Avery; Minhaj, Mohammed; Nizamuddin, Junaid; Wenger, Julia; Mahmood, Eitezaz; Mueller, Ariel; Shaefi, Shahzad; Scavone, Barbara; Kociol, Robb D.; Talmor, Daniel; Rana, Sarosh
Abstract : Objective : The mechanisms leading to worse outcomes in African-American (AA) women with preeclampsia/eclampsia remain unclear. Our objective was to identify racial differences in maternal comorbidities, peripartum characteristics, and maternal and fetal outcomes. Methods/Results : When compared to white women with preeclampsia/eclampsia, AA women had an increased unadjusted risk of inpatient maternal mortality (OR 3.70, 95% CI: 2.19–6.24). After adjustment for covariates, in-hospital mortality for AA women remained higher than that for white women (OR 2.85, 95% CI: 1.38–5.53), while the adjusted risk of death among Hispanic women did not differ from that for white women. We also found an increased risk of intrauterine fetal death (IUFD) among AA women. When compared to white women with preeclampsia, AA women had an increased unadjusted odds of IUFD (OR 2.78, 95% CI: 2.49–3.11), which remained significant after adjustment for covariates (adjusted OR 2.45, 95% CI: 2.14–2.82). In contrast, IUFD among Hispanic women did not differ from that for white women after adjusting for covariates. Conclusions and Relevance : Our data suggest that African-American women are more likely to have risk factors for preeclampsia and more likely to suffer an adverse outcome during peripartum care. Future research should examine whether controlling co-morbidities and other risk factors will help to alleviate racial disparities in outcomes in this cohort of women.